Knowledge-based policy-making and integration: Distinct indication to Tehran. Issue 3 (2nd September 2018) - Daneshpour, Zohreh A.; Mahmoudpour, Asrin; Ebrahimnia, Vahide
ABSTRACT: This paper deliberates on the importance of two major themes, (a) emphasis shift from traditional urban planning approach currently practised in such cities as Tehran to a spatial metropolitan planning, and (b) giving due consideration to the role of knowledge on integrate metropolitan planning. In Tehran, the multiplicity of policy-makers involved in metropolitan planning portrays the unsolvable procedural problems of transfer of knowledge and its impact upon substantive aspects of planning. The purpose of this paper is to study the role of knowledge on integration in spatial metropolitan planning, presuming the necessity of integration in general and in Tehran as a case presented to exemplify the general ideas and challenges of knowledge-based policy integration. A qualitative content analysis was applied to achieve the purpose of this study. Application of the analytic aspect of the proposed framework disclosed the barriers of achieving a spatial integrated knowledge-based planning and policy-making in Tehran.